Integrating Drone Technology in Agricultural Practices: Evidence from Tamil Nadu’s Farmer Producer Organizations - Malaisamy A; Yazhini A; Raswanthkrishna M (Food Science and Agriculture: Research Highlights Vol. 1, 2025)
The advent of drone technology has revolutionized various industries, with agriculture being one of the most significantly impacted sectors. The integration of drones into agricultural practices contributes to environmental sustainability by promoting more efficient use of resources. Indian agriculture makes a substantial contribution to the nation’s GDP, employment, and food security. It directly employs over half of the country’s workforce, supporting the livelihoods of rural communities. Historically, Indian agriculture has been labour-intensive and reliant on traditional practices, resulting in inefficient resource utilization. To address the numerous challenges facing the Indian agriculture sector, the adoption of emerging technologies, such as drones, is imperative. Drones have the capacity to significantly enhance agricultural practices, increasing productivity and reducing resource wastage. This study explores the economic dynamics of drone technology in agriculture, addressing a gap in past research amid the growing use of Artificial Intelligence in the sector. This study integrated the Partial budgeting approach as it allows for assessing the impact of a change in the production system on a farmer’s net income without knowing all costs of production. This study was conducted in two districts of Tamil Nadu using a multistage sampling technique to collect the data. Conducted in the paddy cultivation regions of Thanjavur and Madurai districts in Tamil Nadu, the study involves a sample of 80 for UAV technology and 120 for conventional methods. The findings reveal significant cost savings and higher profitability with drone-assisted farming, where total expenses decrease from Rs.27,723.20 for conventional farming to Rs.22,857.50 for drones, primarily due to reduced pesticide and herbicide use and improved application efficiency. While both methods yield similar gross returns of Rs.39,100 for conventional and Rs.40,640 for drone-assisted-the net returns are markedly higher for drones at Rs.17,782.50 versus Rs.11,376.80 for conventional practices. A per-acre comparison shows substantial reductions in labor costs, with human labor decreasing from Rs.11,077 to Rs.5,628 and pesticide costs falling from Rs.2,032 to Rs.950. Although machine labor costs rise slightly with UAVs, overall savings enhance the financial viability of drone-assisted farming. The partial budget analysis indicates a net profit increase of Rs.7,331, underscoring the economic advantages of adopting drone technology in agriculture. Finally, it is concluded that the integration of drone technology into Indian agriculture, particularly in paddy cultivation in Tamil Nadu’s Thanjavur and Madurai districts, signifies a transformative shift towards more efficient and profitable farming practices.